Promocja wydarzeń marketingowych elementem budowania pozycji konkurencyjnej miasta Opola - Mroczek, Agnieszka (The Promotion of Marketing Events as the Component in Constructing Competitive Position of Opole Town, 2008)
A town constitutes a mega-product, a mutually related set of material products and services, which are available in a town for their users and which result in obtaining additional advantages. The consumption of such a product takes place directly in a town. The due component elements are an image, local cultural climate, enterprising activities, ability for self-fulfilment, communication system, as well as the quality of town management. Marketing events themselves will not result in an inflow of tourist traffic to a town. A proper promotion is a necessary factor. The town of Opole does not represent a typical tourist centre. The town authorities perceive a great opportunity in attracting tourists by means of proper promotion of marketing events. The most important of such events are, among others, National Festival of Polish Song, Theatre Confrontations in Opole, or International Percussion Festival. They are vigorously promoted and they attract most tourists to the town. Promotional activity directly influences the construction of town's positive image, although the research results point to the fact that many tourists associate it mainly with the National Festival of Polish Song. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 160-172